Application of geotechnology to identify vegetation fragments in the municipality of Belém-Pará-Brasil in the year 2020 (Research, Society and Development, 2022)
The general objective of this work is to identify, through the use of geotechnology, areas that have vegetation fragments and environmental conservation areas in the municipality of Belém. To generate maps and perform spatial analyses, two CBERS 04A images were acquired. From the analysis of the data obtained, it was possible to identify the environmental conservation areas of the municipality of Belém and the vegetation fragments, highlighting: the Ecological and Environmental Park of Belém, the State Park of Utinga, the Environmental Protection Area of Metropolitan Region of Belém, the Bosque Rodrigues Alves, the Emílio Goeldi Museum and the Environmental Protection Area of ​​Ilha do Combu, through the results it was verified the importance of geotechnologies for the identification of environmental protection areas, which can also be used with the aim of defining more effective forms of use and occupation of areas of vegetation fragments in Belém and in other municipalities interested in nature conservation.